MANFAAT MEDIA TELEVISI SEBAGAI SARANA PERKEMBANGAN KOGNITIF ANAK USIA DINI - Muzdhalifah (Institut Agama Islam Darul Ulum Kandangan, 2019)
Early childhood cognitive development is formed so quickly in the early stages of the start of human life from the age of 0-6 years, that age is categorized as the golden age or the golden age of the age range called early childhood. Therefore, in order to develop children's cognitive through television media in this digital era, teachers and parents have been widely used. And of course the use of television media as a source of children's learning has a positive impact with a record of proportions, and television channels must always be adjusted to the child's age, so that television media can provide educational pathways and provide benefits for early childhood. The data collection technique in this writing is the library looking at previous studies and then analyzed. From the results of previous research analysis, it can be concluded that television media can be used as a means for early childhood cognitive developmen.